Organizational values perceived by successors of rural properties at cooperative system: Collectivists or individualists? - Teston, Sayonara de Fátima; Zawadzki, Patrick; Lizote, Suzete Antonieta; Gupta, Sandeep Kumar; Reznik, Nadiia (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
The objective was to evaluate the profile of the organizational values perceived by the successors in the decision process on continuity in agribusiness in a cooperative system. The design of the method followed a quantitative, descriptive, survey, and cross-sectional approach. One hundred nineteen successors participated in the study. Descriptive statistics and tests were applied to compare groups and relate dimensions. Successors realize that there is a relationship between collectivist and individualist values in rural property. The undecided ones do not perceive significant differences in values in most of the values. The article demonstrates the need to adapt to the regional cooperative system and rural properties to the associated successors' values.